Clima organizacional y su incidencia en la administración del gobierno autónomo descentralizado municipal del cantón Quevedo año 2021. - Farias Vélez, María Elizabeth (2022)
The objective of this research was to evaluate the incidence of the organizational climate in the administration of the Municipal Decentralized Autonomous Government of the Quevedo canton Year 2021. For this, a survey was applied to a significant sample of the workers of the aforementioned institution that allowed the situational characterization. The results obtained show that currently in the Municipal GAD of the Quevedo canton, there is a high level of development of the organizational climate, so that there is extensive knowledge of the workers about internal policies, system of ladder, product of a time greater than two years in their functions, for which the majority mentioned that they are satisfied with their jobs. Despite acceptable communication between workers and departmental directors, which show the leadership of the latter within the institution, it was also possible to appreciate that this is also a factor that affects the organizational climate of the GAD under study, since with almost half of the workers (47.69%) stated that with little or no frequency good ideas are accepted in the institution. Within the administrative process of the institution under study, it was possible to appreciate the need to establish standards for measurement, correction and feedback of the activities carried out within it, since the control phase expresses more problems in the institution. Continuous training for the workers of the Municipal GAD under study is highlighted as the main motivational factor in the institution, as well as the most acclaimed strategy to improve the development of the organizational climate in the institution.